If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -20 + -2x = 4x + 4 Reorder the terms: -20 + -2x = 4 + 4x Solving -20 + -2x = 4 + 4x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-4x' to each side of the equation. -20 + -2x + -4x = 4 + 4x + -4x Combine like terms: -2x + -4x = -6x -20 + -6x = 4 + 4x + -4x Combine like terms: 4x + -4x = 0 -20 + -6x = 4 + 0 -20 + -6x = 4 Add '20' to each side of the equation. -20 + 20 + -6x = 4 + 20 Combine like terms: -20 + 20 = 0 0 + -6x = 4 + 20 -6x = 4 + 20 Combine like terms: 4 + 20 = 24 -6x = 24 Divide each side by '-6'. x = -4 Simplifying x = -4
| 8n-n=7+8n | | 2y+4w=2 | | 5z=1.4+4.6 | | 4(3x+2)=3(4x-11) | | 13x^2=16x+5 | | x=15.75+3.2(0) | | 10=-z | | -10p-3(3-5p)=3(p-4)-15 | | 7x-1=-8(x+2) | | -7b=-8b | | 3+2n-(n+1)=3n-6 | | (x-2)(x+2)=6 | | 4(2x-3)=3(4x-11) | | -3(y+5)=2y+15 | | 2*=14 | | x^2+95x+96= | | x=15.75+3.2(20) | | -4u+24=-8(u-6) | | 7*8+5x=75x | | 2-3v-3v=6-6v | | 3-2w=2w-5 | | 1+2m=6+2m | | 19v-4v+23=8v-19 | | 6x+2+5x+7=10x+4 | | 5x^2-6x+20=14+11x | | 6x=-24+3a | | H(t)=2000-2t | | 7*8+5x=75 | | 5x^2-3x=x^2+7 | | -121x=8-3x | | 16x-8=16x-16 | | 3x-4-6x+7= |